The Existence of President Instruction of The Republic of Indonesia Number 1 The Year 1991 on The Wide Spread of Compilation of Islamic Law in Indonesian Legal System - Fajar Sugianto; Slamet Suhartono (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2018)
President Instruction Number 1 Year 1991 is a legal instrument that became Indonesia’s positive law regulating the Compilation of Islamic Law (KHI). However, the constitutional system and regulation system in Indonesia have undergone significant changes since the reform era. It raised another legal issue in the application and implementation of the Compilation of Islamic Law since it is not categorized as the source of law in Indonesia’s legal system. It cannot be applied to the government directly because of lack of legal binding. Nevertheless, the existence of the President Instruction still provides recognition through join decision with the Ministry of Religion and the Supreme Court. Thus, the Compilation of Islamic Law can be institutionally applied in the Religious Court which positioned under the Indonesia’s Supreme Court. Since then Judges easily apply the Compilation of Islamic Law as the legal source in resolving disputes in Muslim society. (Inpres 1/1991 merupakan instrumen hukum yang menjadikan hukum Islam sebagai hukum positif di Indonesia, akan tetapi perkembangan sistem ketatanegaraan dan sistem perundang-undangan di Indonesia telah mengalami perubahan yang sangat pesat sejak era reformasi. Hal ini menimbulkan problem hukum baru dalam pemberlakuan Kompilasi Hukum Islam (KHI) mengingat kedudukan Inpres 1/1991 dalam sistem perundang-undangan tidak dikenal sebagai peraturan perundang-undangan. Dalam aspek kekuatan mengikat, Inpres tersebut tidak dapat diberlakukan untuk umum karena tidak mempunyai kekuatan mengikat umum dan hanya bersifat mengikat ke dalam terhadap pejabat yang berkedudukan lebih rendah pada 1 (satu) institusi. Kendatipun demikian eksistensi Inpres 1/1991 hingga hari ini masih diakui keberadaannya mengingat substansinya dibentuk melalui keputusan bersama antara Menteri Agama dengan Ketua Mahkamah Agung. Sehingga, Kompilasi Hukum Islam mengikat hakim-hakim peradilan agama yang berada di bawah lingkungan Mahkamah Agung. Para hakim dapat menggunakan Kompilasi Hukum Islam sebagai dasar hukum untuk menyelesaikan sengketa yang terjadi diantara masyarakat yang beragama Islam)